Evaluation of a DNA Extraction and Purification Protocol Using Archived Formalin-fixed Paraffin-embedded Tissues for BRAF Mutations Analysis in Papillary Thyroid Microcarcinomas. Issue 1 (January 2019) - Nechifor-Boilă, Adela; Loghin, Andrada; Descotes, Françoise; Decaussin-Petrucci, Myriam; Borda, Angela
Abstract : The isolation of good quality genomic DNA from formalin-fixed, paraffin-embedded tissues is challenging, especially in cases of small tissue specimens. The aim of our study was to evaluate a DNA extraction protocol using formalin-fixed, paraffin-embedded tissues in our laboratory and apply this method to a series of papillary thyroid microcarcinomas (PTMCs). A total of 25 PTMCs and 3 papillary thyroid carcinoma control cases were included in the study. We assessed a DNA extraction protocol on the basis of a precipitation method (MasterPure DNA purification kit, Epicentre), according to the manufacturer's instructions. All PTMCs were subject to real-time polymerase chain reaction (PCR) amplification targeting the BRAF gene and a housekeeping gene ( GAPDH ). BRAF gene mutations were then assessed by high-resolution melting analysis and confirmed by sequencing of the PCR products. Using this extraction method, we produced good yields of DNA (mean concentration, 147.4±77.8 ng/µL), in addition to high levels of purity (mean A260/A280 ratio: 1.63±0.1). We successfully assessed the BRAF mutation status in 24 cases (16 BRAF -negative; 8 BRAF V600E positive), although 1 case revealed an inconclusive pattern following high-resolution melting analysis and sequencing of the PCR products. We observed no differences in the tumor size ( P =0.693), storage period of the tumor block ( P =0.282), DNA concentration ( P =0.243), DNA purity ( P =0.458), Cp GAPDH ( P =0.173), or Cp BRAF ( P =0.217) values between the BRAF -mutated and nonmutated group of PTMCs. Our findings demonstrate the importance of a reliable, reproducible DNA extraction technique for efficient PCR amplification, uniformly applied to all cases in this study, regardless of the BRAF mutation status.